Psychological Underpinnings of Digital Investing: The Interplay Between Behavioral Biases and Financial Self-Efficacy - Agustina; Fandi Halim (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to analyze the influence of behavioral bias and financial self-efficacy on individual investment decisions, particularly among the younger generation engaged in digital investment. This study used a quantitative explanatory approach involving 400 respondents who are active investors on digital platforms. Data were collected through questionnaires and data analysis techniques using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results show that behavioral biases, namely cognitive bias and emotional bias, and financial self-efficacy have a positive and significant influence on investment decisions. These results explain that investor behavior in the digital capital market is not entirely based on rational considerations, but is heavily influenced by internal factors such as emotional drives and self-confidence in personal financial capabilities. This research is expected to be useful in the development of educational features and investor protection policies to minimize impulsive actions in young investors.